2021
DOI: 10.1111/nph.17211
|View full text |Cite
|
Sign up to set email alerts
|

The miR172/IDS1 signaling module confers salt tolerance through maintaining ROS homeostasis in cereal crops

Abstract: Salt stress triggers the overdose accumulation of reactive oxygen species (ROS) in crop plants, leading to severe oxidative damage to living tissues. MicroRNAs (miRNAs) act as master regulators orchestrating the stress responsive regulatory networks as well as salt tolerance. However, the fundamental roles of miRNAs in modulating salt tolerance in cereal crops, especially in salt-triggered ROS scavenging remain largely unknown. Through small RNA sequencing, a salt-responsive miRNA, miR172 was identified in ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 68 publications
(79 reference statements)
7
56
0
Order By: Relevance
“…The overexpression of soybean miR172c improves tolerance to drought and salinity stress, and it also enhances sensitivity to ABA in transgenic A. thaliana plants ( Li et al, 2016 ). Recently, Cheng et al (2021) found that miR172s (mainly miR172a and miR172b) act as a positive regulator of salt tolerance in rice and wheat. Further, it also maintains the ROS homeostasis during salt stress, generally by balancing the expression of several ROS-scavenging-related genes in both wheat and rice ( Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of soybean miR172c improves tolerance to drought and salinity stress, and it also enhances sensitivity to ABA in transgenic A. thaliana plants ( Li et al, 2016 ). Recently, Cheng et al (2021) found that miR172s (mainly miR172a and miR172b) act as a positive regulator of salt tolerance in rice and wheat. Further, it also maintains the ROS homeostasis during salt stress, generally by balancing the expression of several ROS-scavenging-related genes in both wheat and rice ( Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cheng et al (2021) found that miR172s (mainly miR172a and miR172b) act as a positive regulator of salt tolerance in rice and wheat. Further, it also maintains the ROS homeostasis during salt stress, generally by balancing the expression of several ROS-scavenging-related genes in both wheat and rice ( Cheng et al, 2021 ). The transgenic B. napus plants overexpressing miR395 indicated a lower degree of cadmium-induced oxidative stress compared to wild-type plants ( Zhang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rice, the Osa‐ mir172 / IDS1 ( INDETERMINATE SPIKELET1 ) module plays a key role in maintaining ROS homeostasis under salt stress by deregulating the expression of multiple genes encoding detoxification enzymes. The mir172/IDS1 module is also conserved in the cereals and regulates the expression of TaAPX2/5/7/8 , TaGPX1/2/3 , and TaCAT2/4 in wheat (Cheng et al, 2021). In contrast, Arabidopsis lines overexpressing ghrmiR414c exhibited reduced seed germination, seedling biomass, and primary root elongation under salt stress due to the down‐regulation of its target GhFSD , which encodes a Fe‐SOD (Wang et al, 2019).…”
Section: Role Of Rsrnas For Mediating Salt Tolerance In Plantsmentioning
confidence: 99%
“…CRISPR-Cas based genome editing technology presents a powerful genetic knockout approach to study the function of coding genes and non-coding genes in plants (Bi et al, 2020;Cheng et al, 2021;Liu et al, 2020a;Miao et al, 2019Miao et al, , 2020Ren et al, 2019Ren et al, , 2021Tang et al, 2019;Wang et al, 2019;Zhong et al, 2019Zhong et al, , 2020Zhou et al, 2021). Previously, we successfully applied CRISPR-Cas9 to knock out multiple miRNAs in rice, which provided multiple insights in miRNA genesis and complex regulation (Zhou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%